2014
DOI: 10.3189/2014aog66a123
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of discharge from Langtang River basin, Rasuwa, Nepal, using a glacio-hydrological model

Abstract: This paper provides the results of semi-distributed positive degree-day (PDD) modelling for a glacierized river basin in Nepal. The main objective is to estimate the present and future discharge from the glacierized Langtang River basin using a PDD model (PDDM). The PDDM is calibrated for the period 1993-98 and is validated for the period 1999-2006 with Nash-Sutcliffe values of 0.85 and 0.80, respectively. Furthermore, the projected precipitation and temperature data from 2010 to 2050 are obtained from the Bje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 13 publications
4
17
0
Order By: Relevance
“…Glaciers melt is estimated to contribute 26% and 3% of total runoff in Indus basin and Ganga Basin respectively (Immerzeel and Bierkens, 2012). A few studies, including Alford and Armstrong (2010), Pradhananga et al (2014), andTahir et al (2015) have looked at hydrological impacts on smaller sub-basins. Tahir et al (2011) found that (a) a 1% increase in snow cover area in Hunza under constant temperature will increase summer discharge by 0.7%, (b) an increase in 1 • C mean temperature (keeping precipitation and snow cover constant) is expected to increase summer discharge by 33%, and (c) a 20% increase in snow cover in combination with a 2-4 • C rise in mean temperature is expected to increase future stream flows by 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Glaciers melt is estimated to contribute 26% and 3% of total runoff in Indus basin and Ganga Basin respectively (Immerzeel and Bierkens, 2012). A few studies, including Alford and Armstrong (2010), Pradhananga et al (2014), andTahir et al (2015) have looked at hydrological impacts on smaller sub-basins. Tahir et al (2011) found that (a) a 1% increase in snow cover area in Hunza under constant temperature will increase summer discharge by 0.7%, (b) an increase in 1 • C mean temperature (keeping precipitation and snow cover constant) is expected to increase summer discharge by 33%, and (c) a 20% increase in snow cover in combination with a 2-4 • C rise in mean temperature is expected to increase future stream flows by 100%.…”
Section: Introductionmentioning
confidence: 99%
“…to 7215 m a.s.l. [20]. The glaciers of this catchment cover an area of 137.5 km 2 while the remaining area of 216.1 km 2 is covered by rock and vegetation.…”
Section: Study Areamentioning
confidence: 99%
“…The second method uses a degree day factor adjusted for the elevation effect (Pradhananga et al, 2014) while the third method uses aspect and elevation modified degree day factors. There is variation of degree day factor with respect to the location of glacier cover.…”
Section: Modelling Approachmentioning
confidence: 99%
“…Below 5000 m, DDFs is 5 mm d -1 o C -1 , and DDFi is set to 6 mm d -1 o C -1 . Above 5000 m, DDFs is set to 6.5 mm d -1 o C -1 and DDFi 7.5 mm d -1 o C -1 for ice ablation above 5000 m. These values are calibrated according to the range of degree day factor provided (Pradhananga et al, 2014). For debris covered glacier in the basin, a melt reduction factor of 0.5 is applied (Kayastha et al, 2000b).…”
Section: Modelling Approachmentioning
confidence: 99%